Sustainable Product Innovation and Consumer Demand in EU Market for Sustainable Products: Array - Ngwakwe, Collins (Acta Universitatis Danubius. Œconomica, 2020)
the industry and consumers have a role toward the actualisation of sustainable economy; sustainable product innovation and consumer sustainable purchasing are important avenues. Objective: This paper examines the relationship between sustainable product innovation and consumer patronage of sustainable products. Prior Work: the paper is inclined on the concept of sustainable production. Approach: Data were collected from the index of European Union Market for Sustainable Products. The data on sustainable sourcing, sustainable production strategy and consumer purchase of sustainable products were analysed using the fixed and random effects panel regression. Finding: results from the analysis indicate a significant positive relationship between sustainable sourcing, sustainable production strategy and consumer purchase at a p-value of less than 0.001. Implication: Producers of can improve sales of sustainable products by improving sustainable sourcing and production strategy. The paper provides academic case study for sustainable business and further research agenda is suggested to explore aspects of sustainable products most preferred by consumers. Value: this paper provides first empirical link between the EU data on sustainable sourcing and consumer patronage and provides initial result, which indicates that random effect regression provides a better model for this analysis.